Žarnica - Južnič, Stanislav (Vakuumist, 1997)
We describe the invention of the incandescent light, mostly after Edison's experiments in vacuum. In the first part of this article we are dealing with the inventions made in USA.
Keywords: fizika; physics; žarnica; odkritja